A rare case of Herlyn-Werner-Wunderlich syndrome-with pregnancy - Vikas Deswal; Nauratmal Kumawat; Sunita Purohit; Rajendra Jat (The Egyptian Journal of Radiology and Nuclear Medicine, 2016)
Herlyn-Werner-Wunderlich syndrome also known as uterus didelphys with obstructing hemivaginal septum and ipsilateral renal agenesis (OHVIRA) is a very rare syndrome with only a few case reported. A female patient referred to our hospital with retention of urine revealed uterus didelphys with 8 weeks gestation sac in the left moiety and hematometra and hematocolpous in the right moiety with absent right kidney. Diagnosing this syndrome at an early stage is important to prevent the complications in these patients.